Methionine synthase A2756G and reduced folate carrier1 A80G gene polymorphisms as maternal risk factors for Down syndrome in Egypt - Maha Moustafa; Elham Gaber; Gamal Abo El Fath (Egyptian Journal of Medical Human Genetics, 2016)
Background: Polymorphisms of genes encoding enzymes involved in folate metabolism have long been hypothesized to be maternal risk factors for Down syndrome, however, results are conflicting and inconclusive. Aim of the study: To analyze the effect of methionine synthase (MTR) A2756G, and reduced folate carrier (RFC1) A80G gene polymorphisms on the maternal risk for DS. Patients: This study was conducted in the Medical Genetics Center, Ain-Shams University hospitals, on a total of 170 mothers of children, diagnosed with Down syndrome, who were attending the center. Eighty-five control mothers were also enrolled in the study. Methods: Genotype analyses were performed using PCR-RFLP to detect RFC1A80G and MTRA2756G gene polymorphisms in all case and control mothers. Results: Comparing RFC1A80G genotype frequency between both groups revealed, that the frequency of the AA genotype in case mothers (94.11%) is highly significantly (p < 0.001) greater than its frequency in control mothers (74.11%), with no significant difference between the two groups regarding GG genotype. Comparing RFC1 A80G allele frequency between the two groups revealed a high frequency of the A allele among case mothers (94.11%), which showed a highly statistically significant difference (p < 0.001) from the control group (55.29%), meanwhile the G allele showed a low frequency of 5.88% in DS mothers compared to 22.35% in the control mothers, with a highly statistically significant difference (p < 0.001) between the two groups. Regarding MTRA2756G polymorphism, it was found that the AA genotype predominated in the control group (65.88%) with a highly statistically significant difference (p < 0.001) from case mothers group (5.88%). Comparing MTR allele frequency between the two groups revealed predominance of the G allele among mothers of DS children (76.47%). Conclusion: Current results provide strong evidence that the MTRA2756G, and RFC1 80 A genotypes could be considered as maternal risk factors for DS in Egyptian mothers.